INFLUÊNCIA DE GENÓTIPOS DE ALGODOEIRO SOBRE O DESENVOLVIMENTO E CAPACIDADE PREDATÓRIA DE NINFAS DE PODISUS NIGRISPINUS (DALLAS, 1851)1 - Boiça, A.l. [UNESP]; Santos, T.m. Dos [UNESP]; Soares, J.j. (Instituto Biológico, 2024)
The development and predatory capacity of Podisus nigrispinus (Dallas, 1851) nymphs fed on Alabama argillacea (Hübner, 1818) larvae reared on cotton genotypes CNPA Precoce 1, CNPA 9211-31, CNPA 9211-41 e GL2 GL3 were studied. The duration and survival of instars of P. nigrispinus nymphs were not influencied by cotton genotypes used to feed for the prey A. argillacea. During the nymphal phase of P. nigrispinus, the highest consumption of A. argillacea larvae, 16.5 and 15.9 was observed when nymphs fed on larvae reared on, respectivelly, CNPA 9211-41 and CNPA 9211-31 genotypes. It was observed compatibility between use of plant resistance and biological control since P. nigrispinus showed the highest consumption rate when was fed on A. argillacea larvae reared on resistant cotton genotypes leaves.

Estudou-se o desenvolvimento e capacidade predatória de ninfas de Podisus nigrispinus (Dallas, 1851) alimentadas com lagartas de Alabama argillacea (Hübner, 1818) criadas em folhas de algodoeiro dos genótipos CNPA Precoce 1, CNPA 9211-31, CNPA 9211-41 e GL2 GL3. A duração e a sobrevivência dos ínstares de P. nigrispinus não foram influenciadas pelos genótipos de algodoeiro oferecidos como alimento à sua presa A. argillacea. Durante a fase ninfal de P. nigrispinus, o consumo de lagartas de A. argillacea foi maior, 16,5 e 15,9, respectivamente, quando as ninfas foram alimentadas com lagartas criadas em folhas dos genótipos CNPA 9211-41 e CNPA 9211-31. O maior consumo pelo predador P. nigrispinus de lagartas de A. argillacea, criadas em folhas de algodoeiro dos genótipos resistentes, indicou compatibilidade entre a utilização de plantas resistentes e o controle biológico.
INFLUENCE OF COTTON GENOTYPES ON DEVELOPMENT AND PREDATORY CAPACITY OF PODISUS NIGRISPINUS (DALLAS, 1851) NYMPHS
Keywords: Cotton leafworm; predator; plant resistance; biological control; tritrophic interaction.; Curuquerê-do-algodoeiro; predador; resistência de plantas; controle biológico; interação tritrófica.